Fasilitas Belajar Tata Hidang di Workshop terhadap Hasil Belajar Siswa XI Kuliner SMKN 6 Padang - Putri, Dian Mutiara; Andriani, Cici; Elida, Elida; Indrayeni, Wiwik (Lembaga Yasin AlSys, 2025)
This research is motivated by the importance of learning facilities in supporting the learning process of housekeeping practice at SMK, especially at SMKN 6 Padang. The gap found is that there is still a lack of optimal utilization of facilities in the workshop which has an impact on student learning outcomes. This study aims to determine the effect of culinary learning facilities available in the workshop on the learning outcomes of Culinary XI class students of SMKN 6 Padang. This research is a quantitative study with a simple linear regression approach. The research was conducted at SMK Negeri 6 Padang on grade XI students of the Culinary expertise program, after the author conducted a proposal seminar. The population in this study were all students of class XI Culinary totaling 101 people. The sampling technique used is probability sampling, which is a sampling technique that provides an equal opportunity for each member of the population to be selected as a sample. The number of samples in this study was determined using the Yamane formula (Sugiyono, 2019: 158), and rounded up to 50 respondents. Based on the results of research on the effect of learning facilities in the workshop on the learning outcomes of Culinary class XI students of SMKN 6 Padang, it can be concluded that learning facilities have an important role in supporting the success of practical learning.